Radiation pneumonitis following Yttrium-90 radioembolization: A Korean multicenter study - Kim, Hyo-Cheol; Kim, Gyoung Min (Frontiers in Oncology, 2023)
Objective To report the incidence of radiation pneumonitis after radioembolization. Methods In this retrospective study, from May 2009 to July 2021, 782 consecutive patients underwent radioembolization in two institutes. Medical internal radiation dose dosimetry and partition dosimetry were used for glass and resin Yttrium-90-labeled microspheres (90Y-microspheres), respectively. Medical records and radiological findings were retrospectively evaluated with emphasis on the symptomatic radiation pneumonitis. Results Of the 732 patients with lung shunt study and follow-up, 13 (1.8%) had symptomatic radiation pneumonitis and six patients died due to radiation pneumonitis. Of the 721 patients whose lung doses were calculated, 10 patients who were treated with glass (n = 5) and resin (n = 5) 90Y-microspheres had radiation pneumonitis. No significant statistical difference between glass and resin 90Y-microspheres (p = 0.304) was noted in terms of radiation pneumonitis incidence. Among the patients with radiation pneumonitis, all five patients treated with glass 90Y-microspheres had estimated lung doses > 29 Gy, whereas five patients treated with resin 90Y-microspheres had relatively wide range of lung dose reaching much lower value (13.21Gy). Conclusion The present study suggests that radiation pneumonitis after radioembolization may occur even though the manufacturer’s instructions are followed.